Aktivitas Fraksi Nonpolar dari Ekstrak Etanol Akar Dadangkak (Hydrolea spinosa L.) terhadap Penurunan Kadar Glukosa Darah Tikus Jantan yang Diinduksi Aloksan - Muhammad Zaini; Vivi Shofia; Amalia Ajrina (Jurnal Farmasi Indonesia, 2018)
The roots of Dadangkak (Hydrolea spinosa L.) empirically have been used by Kalimantan people to cure diabetes. The purpose of this research is to examine the effect of fractions ratio from ethanol extract. The research started from extraction of the roots of Dadangkak (250 grams) by materation using ethanol. From that extraction yielded 16.62 grams of ethanol extract. Ethanol extract had been fractionated with n-hexane and petroleum ether. The antidiabetic assay using 20 Wistar mice that had been divided into 4 groups : Aquadest 2 ml/200 grams of weight is given to the first group, Glibencalmide 0.45 mg/kg BW is given to the second group, n-hexane fraction 100 mg/kg BW is given to the third group and petroleum eter 100 mg/kg BW is given to the forth group. Before all of groups had been given treatments, the mice had been induced by Aloxan 150 mg/kg BW intraperitoneally. The forth day after being induced, mice also given control and fractions treatments for 7 days perorally. The measurement of blood glucose level had been done at the first, forth, and twelfth day after being induced using Gluco-DR. The blood glucose level had been tested by SPSS with 95% confidence level. The result of this research showed the average of blood glucose level by the n-hexane fraction is 189,8 ± 13,59 mg/dL and petroleum ether is 437,6 ± 8,98 mg/dL. n-hexane fraction could decrease the blood glucose level of mice significantly (sig<0.05) compared to the control group. On the other side, the giving of petroleum ether fraction is not showing the decrease of blood glucose level significantly (sig>0.05).